2012
DOI: 10.1152/physiolgenomics.00032.2011
|View full text |Cite
|
Sign up to set email alerts
|

Multiple effects of a short-term dexamethasone treatment in human skeletal muscle and adipose tissue

Abstract: Glucocorticoids are frequently prescribed drugs with important side-effects such as glucose intolerance and tissue remodeling. The goal was to explore the molecular basis of the response of skeletal muscle and adipose tissue during a short-term dexamethasone treatment to better understand the induction of side-effects of glucocorticoids on these metabolic tissues. Fifteen healthy male subjects were assigned to a 4-day treatment with dexamethasone at 4 mg/day. The primary outcome measures were changes in gene e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…Glucocorticoids are commonly prescribed for the treatment of several situations of inflammatory disorders; nevertheless, there are plenty of undesirable side effects associated with both acute and long term treatments [29]. For this reason, we believe that glycerolipids and MGDGs may constitute an alternative to common anti-inflammatory drugs, as they present a good therapeutic activity without known side effects.…”
Section: Resultsmentioning
confidence: 99%
“…Glucocorticoids are commonly prescribed for the treatment of several situations of inflammatory disorders; nevertheless, there are plenty of undesirable side effects associated with both acute and long term treatments [29]. For this reason, we believe that glycerolipids and MGDGs may constitute an alternative to common anti-inflammatory drugs, as they present a good therapeutic activity without known side effects.…”
Section: Resultsmentioning
confidence: 99%
“…Further evidence that dexamethasone can play a role in cell migration was demonstrated by its effects on augmenting the actions of the chemokine receptor, CXCR4 on T cells [74]. A recent study conducted in healthy males revealed elevated inflammatory responses in skeletal and adipose tissue following acute dexamethasone treatment [75]. Given strong evidence exists that peripheral neuropathy in rodent models leads to a weakened blood-spinal barrier with robust chemokine/proinflammatory cytokine signaling and infiltration of activated macrophages [10], it is possible that acute i.t.…”
Section: Discussionmentioning
confidence: 99%
“…GR is an important transcription factor in neurons and is known to exert effects on neuronal structure and plasticity. So far the focus on GR-mediated action of glucocorticoids in a neuronal context has remained largely in the dark and most of the knowledge on GR modes of action, GR responsive genes and pathways and crosstalk partners of GR has come from studies on peripheral tissues including the immune system, the respiratory tract, skeletal muscle and adipose tissue as well as various types of cancer cells [40-42]. Approximately 1,100 genomic binding sites of GR were identified in neuronal PC12 cells, the majority of which are novel and display only very limited overlap with GR binding sites in other non-neuronal cell types.…”
Section: Discussionmentioning
confidence: 99%